Self-regulation and self-efficacy of EFL learners in hybrid educational settings in Türkiye - Kaptanoglu, Mehmet Yagiz; Kavanoz, Suzan (WILEY, 2024)
Distance learning, online learning and hybrid learning models have been a part of language education for a long time. The adoption of these models and research focusing on related phenomena have become even more frequent since the breakout of the COVID-19 pandemic in 2019. This mixed-method study examines the relationship between online learning self-efficacy and online self-regulation of preparatory class English as a Foreign Language (EFL) learners to provide a picture of the learners' perspective regarding the online segment of the hybrid education system that was in effect during the mentioned era, to provide deeper insights regarding learner perceptions during such times of emergency. Turkish adaptations of the Online-Learning Self-Efficacy Scale and Online Self-regulated Learning Questionnaire were utilized as data collection instruments. To validate and expand the content of quantitative findings, semi-structured interviews were conducted with a selected group of participants. The findings reveal that preparatory year Turkish EFL learners perceive themselves to be self-efficacious and self-regulated at a satisfactory level in online learning environments. The study provides insight into the learners' perceptions during this period and contributes to filling a significant gap within the field as well as offering new perspectives in case we face similar conditions in the future. Learners who perceive themselves as self-efficacious in online learning environments often perceive themselves to be self-regulated as well. This supports the argument that the two concepts of self-efficacy and self-regulation are correlated. Majority of students in higher education context prefer face-to-face learning over online learning or hybrid learning. Given its crucial role in online learning environments, self-regulatory behavior and strategies should be emphasized and supported.
Keywords: foreign language education; hybrid education; online learning; self-efficacy; self-regulation; SATISFACTION; RELIABILITY; STUDENTS; PERCEPTIONS; ADAPTATION; VALIDITY; TURKISH; Psychology